2005
DOI: 10.2991/jnmp.2005.12.s1.18
|View full text |Cite
|
Sign up to set email alerts
|

Explicit integration of the Hénon-Heiles Hamiltonians 1

Abstract: We consider the cubic and quartic Hénon-Heiles Hamiltonians with additional inverse square terms, which pass the Painlevé test for only seven sets of coefficients. For all the not yet integrated cases we prove the singlevaluedness of the general solution. The seven Hamiltonians enjoy two properties: meromorphy of the general solution, which is hyperelliptic with genus two and completeness in the Painlevé sense (impossibility to add any term to the Hamiltonian without destroying the Painlevé property).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 41 publications
0
26
0
1
Order By: Relevance
“…It converts the local information into the global one and can be used not only as an alternative to the standard method, but also as an addition to it, which assists to find solutions of the obtained algebraic system. We have demonstrated that one can find elliptic solutions of the generalized Hénon-Heiles system solving only linear equations and nonlinear equations in one variable, instead of nonlinear system (11). At the same time, to use this method one has to know not only an algebraic system, but also the differential equations from which this system has been obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It converts the local information into the global one and can be used not only as an alternative to the standard method, but also as an addition to it, which assists to find solutions of the obtained algebraic system. We have demonstrated that one can find elliptic solutions of the generalized Hénon-Heiles system solving only linear equations and nonlinear equations in one variable, instead of nonlinear system (11). At the same time, to use this method one has to know not only an algebraic system, but also the differential equations from which this system has been obtained.…”
Section: Resultsmentioning
confidence: 99%
“…The general solutions of the Hénon-Heiles system are known only in integrable cases [37,38,11], in other cases not only four-, but even three-parameter exact solutions have yet to be found. The generalized Hénon-Heiles system has attracted enormous attention over the years and has used as a model in astronomy [30] and in gravitation [25,32].…”
Section: The Hénon-heiles Systemmentioning
confidence: 99%
“…The integrability and non-integrability related to the Hénon-Heiles problem with some parameters and with D = 0 has been considered by many authors, as for example, [8], [9], [13], [15], [17], [18], [22], [23], [28].…”
Section: Introductionmentioning
confidence: 99%
“…3, we recall all the cases (three "cubic" and four "quartic") where the most general classical timeindependent Hamiltonian with two degrees of freedom can have a single-valued general solution. Discarding the integrated cases (see [2] for a review of the current state of this problem), we then focus on the three cases (all "quartic") where the general solution is still missing, aiming to find their general solution.…”
Section: Introductionmentioning
confidence: 99%